2020
DOI: 10.3389/fphar.2020.571156
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Corticosteroid Treatment in Patients With COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background: COVID-19 is a type of pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection that was identified in December 2019. Corticosteroid therapy was empirically used for clinical treatment in the early stage of the disease outbreak; however, data regarding its efficacy and safety are controversial. The aim of this study was to evaluate the efficacy and safety of corticosteroid therapy in patients with COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…Meta-analysis by Pei et al 20 included 5 retrospective studies in 943 patients and concluded that corticosteroids use might increase risk of death (OR: 2.43; 95% CI: 1.44–4.1; P = 0.0001). Similarly, in another meta-analysis based on cohort studies and case series, Cheng et al 21 also concluded that corticosteroids were not effective to decrease mortality, shorten duration of symptoms, or virus clearance time. Of note, both of these two meta-analyses included non-RCTs but observational studies, which had diverse confounding or bias, such as residual confounding, survivor bias, treatment selection bias, collectively decreasing the quality of the conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…Meta-analysis by Pei et al 20 included 5 retrospective studies in 943 patients and concluded that corticosteroids use might increase risk of death (OR: 2.43; 95% CI: 1.44–4.1; P = 0.0001). Similarly, in another meta-analysis based on cohort studies and case series, Cheng et al 21 also concluded that corticosteroids were not effective to decrease mortality, shorten duration of symptoms, or virus clearance time. Of note, both of these two meta-analyses included non-RCTs but observational studies, which had diverse confounding or bias, such as residual confounding, survivor bias, treatment selection bias, collectively decreasing the quality of the conclusion.…”
Section: Discussionmentioning
confidence: 97%
“…Table 3 summarizes the characteristics and main finding from 13 systematic reviews and meta-analyses published since March 2020 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 . Two of these systematic reviews included only randomized controlled trials 76 , 77 .…”
Section: Summary Of the Clinical Evidence Of Corticosteroids Effects mentioning
confidence: 99%
“…In the light of these properties, systemic CSs have been empirically used to manage the cytokine storm in COVID-19 patients and mitigate its most severe manifestations such as ARDS, systemic organ failure and death [ 103 , 104 ]. In the early days of this pandemic, guidance regarding CSs was mixed: on the one hand, data collected during previous coronavirus outbreaks that share many clinical characteristics with COVID-19, SARS and MERS, were inconclusive about efficacy and safety of CSs [ 66 , 105 , 106 , 107 ]; on the other hand, the initial clinical experience on adjunctive therapy with CSs, which was essentially documented by case reports, observational and small (and often single-center) studies, similarly emphasized the need for large scale randomized trials to properly assess CSs on outcomes according to severity of COVID-19 disease [ 51 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. On 6 June 2020, breaking news from the RECOVERY ( R andomized E valuation of COV ID-19 th ER ap Y ) trial based in the United Kingdom (NCT04381936) announced that participants who received 6 mg dexamethasone daily for 10 days saw improvements, and in particular the subsets of patients already on ventilators or who required non-invasive oxygen therapy [ 117 ].…”
Section: Css Use During Covid-19 Pandemic: Pros and Consmentioning
confidence: 99%